2017
DOI: 10.22159/ijpps.2017v9i5.17584
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Activity of Fractional Flower Extracts of Mirabilis Jalapa Against Aluminium Hydrochloride Induced Neurotoxicity in Male Wister Rats

Abstract: Objective: The major objective of this present study was to evaluate the neuroprotective effect of fractional flower extracts (acetone, petroleum ether, methanol and aqueous) of Mirabilis jalapa (MJ) against aluminium hydrochloride-induced neurotoxicity in male wister rats. Methods:From the different fractional flower extracts of Mirabilis jalapa (MJ), two doses (250 and 500 mg/kg body weight) of each extract was initially selected and administered per orally 30 min prior to aluminium hydrochloride administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Previous reports suggest that neurodegeneration and neuronal damage are associated with impaired memory function in rodents [5,10], besides indicating enhanced oxidative stress as an important contributing factor for neurodegeneration [5,10]. Neuroprotective potential of herbal interventions has been reported to be associated with the improved behavior functions [5,10,[29][30][31][32][33]. Our results are in line with these findings, and we have demonstrated that treating hypoxic animals with plant extract improved neuronal morphology and rescued them from degenerative changes.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports suggest that neurodegeneration and neuronal damage are associated with impaired memory function in rodents [5,10], besides indicating enhanced oxidative stress as an important contributing factor for neurodegeneration [5,10]. Neuroprotective potential of herbal interventions has been reported to be associated with the improved behavior functions [5,10,[29][30][31][32][33]. Our results are in line with these findings, and we have demonstrated that treating hypoxic animals with plant extract improved neuronal morphology and rescued them from degenerative changes.…”
Section: Discussionsupporting
confidence: 91%
“…A 10% (w/v) homogenate of brain samples (0.1 M sodium phosphate buffer, pH 7.4) were prepared using homogenizer and then centrifuged at 4000 rpm for 10 min at 4°C. The supernatant homogenate was used to measure, total protein content (Spinreact), and the activities of CAT, SOD, GSH, and LPO based on the standard methods [21][22][23][24].…”
Section: Estimation Of the Endogenous Antioxidant Enzymes And Lipid Pmentioning
confidence: 99%